Immune Response in Preleukemic Mice - Frey-Wettstein, Manuel (1970)
Humoral and cellular immunity was assessed serially in preleukemic AKR mice and Gross virus-injected C3H/HeJ mice over a period of 10 to 12 months. Quantitative gamma globulin, hemagglutinin and hemolysin titers after immunization with sheep red blood cells, and macrophage-migration inhibition were determined. Normal production of gamma globulins as well as humoral antibodies was found in both of these experimental groups of mice, whereas macrophage-migration inhibition, which is believed to be a correlate of cellular immunity, appeared to be abnormal throughout the life of these animals, which were destined to develop a high incidence of lymphoma. Some aspects of this apparent dissociation between humoral and cellular immune response are discussed with regard to the mouse virus lymphoma system, primarily involving the thymus, which was used in these studies.